Seaweed Cellulose: A Hybrid Systematic Literature Review and Bibliometric Analysis - Atina Tri Hapsari; Evi Liviawaty (BIORE Scientia Publisher, 2026)
This study presents a systematic literature review and bibliometric analysis of research developments on seaweed cellulose, highlighting global publication trends, research theme evolution, and scientific collaboration networks throughout the 2015-2025 period based on Scopus indexed publication data. The analysis was conducted using VOSviewer software to map research productivity growth, keyword interconnections, collaboration networks between authors, and the geographical distribution of contributing countries and institutions. The results of the study show a significant increase in the number of publications after 2020, reflecting increased academic and industrial interest in cellulose derived from seaweed as a sustainable and environmentally friendly alternative to cellulose from land plants. Most of the research comes from Asia, particularly China, India, and Indonesia, which have abundant marine resources and strong support for the development of marine biotechnology. Research developments show a shift from basic studies focusing on extraction and characterization to advanced applications, such as biomedicine, bioplastics, and environmentally friendly packaging. This study also identifies gaps in terms of extraction efficiency, product scale, and analysis of seaweed cellulose structure. From the results of this analysis, it can be concluded that the direction of research on seaweed cellulose is increasingly moving towards environmentally friendly product innovation and sustainable biomaterials.